Pengaruh Latar Belakang Pendidikan dan Penempatan Pegawai Terhadap Motivasi Kerja: (Studi pada Dinas Pertanian Kabupaten Pangandaran) - Iing Mulyadi; Enas Enas (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
This study was initiated because of the problem of decreasing employee work motivation. So the purpose of this study is to determine and analyze the effect of educational background on work motivation at the Pangandaran Regency Agriculture Service. To determine and analyze the effect of employee placement on work motivation at the Pangandaran Regency Agriculture Service. To determine and analyze the effect of educational background and employee placement on work motivation at the Pangandaran Regency Agriculture Service. The method used in this study is qualitative descriptive research. Based on the results of the study and discussion, the following conclusions were obtained: Educational background tends to be quite strong, and work motivation tends to be quite strong, so the effect of educational background on work motivation is quite strong. This means that if the educational background is strong enough, work motivation will also increase quite strongly. Employee placement tends to be quite strong, and work motivation tends to be quite strong. The effect of employee placement on work motivation is in the category of quite strong. This means that if employee placement is strong enough, work motivation will also increase quite strongly. Educational background and employee placement have a positive relationship with the work motivation of the Pangandaran Regency Agriculture Service which is quite strong. While the effect of educational background and employee placement on work motivation is in the category of quite strong. This means that there is a fairly strong influence from educational background and employee placement on work motivation